2008
DOI: 10.1136/bmj.39475.498090.80
|View full text |Cite
|
Sign up to set email alerts
|

Presumed consent for organ donation

Abstract: Is an ethical and effective way of dealing with organ donation shortages

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 2 publications
0
18
0
Order By: Relevance
“…In Islam, it is fundamentally wrong to procure organs without prior permission of the deceased or a surrogate (Aksoy, 2001). Nevertheless, there has been global pressure to introduce presumed consent for organ donation (Hamm & Tizzard, 2008;House of Lords European Union Committee, 2008;Howard, 2007). Within the presumed consent legislation, the default rule would be an implied agreement and consent to remove organs unless the individual has opted out by documented written refusal of donation.…”
Section: Islam and The Consenting Process For Organ Donationmentioning
confidence: 98%
See 1 more Smart Citation
“…In Islam, it is fundamentally wrong to procure organs without prior permission of the deceased or a surrogate (Aksoy, 2001). Nevertheless, there has been global pressure to introduce presumed consent for organ donation (Hamm & Tizzard, 2008;House of Lords European Union Committee, 2008;Howard, 2007). Within the presumed consent legislation, the default rule would be an implied agreement and consent to remove organs unless the individual has opted out by documented written refusal of donation.…”
Section: Islam and The Consenting Process For Organ Donationmentioning
confidence: 98%
“…Within the presumed consent legislation, the default rule would be an implied agreement and consent to remove organs unless the individual has opted out by documented written refusal of donation. Presumed consent for organ donation has been advocated in the United Kingdom (Hamm & Tizzard, 2008) and enacted in several European Union countries (e.g., Spain, Portugal, and Austria) (Mossialos, Costa-Font & Rudisill, 2008). A UK survey of Muslims found strong objections to presumed consent for organ donation (Alkhawari, Stimson & Warrens, 2005).…”
Section: Islam and The Consenting Process For Organ Donationmentioning
confidence: 98%
“…Mossialos et al [1] found that that the willingness to donate organs in EU countries was determined by (1) the type of organ donation legislation (unenforced pre- Yes, no, or don't know sumed consent, enforced presumed consent, and informed consent) and (2) respondents' awareness of the type of the legislation. Respondents in countries with an unenforced presumed consent policy had a higher willingness to donate organs than did respondents in countries with an informed consent policy; those in countries with enforced presumed consent policies were most likely to indicate that they would donate organs.…”
Section: Institutional Legislations and Enforcementmentioning
confidence: 98%
“…To increase the supply of transplantable organs, several countries in the European Union (EU) have implemented and are enforcing presumed consent policies for organ donation [1,2]. In countries with informed consent or optin legislation, such as the United Kingdom, Germany, and Sweden, individuals or their family members must give explicit permission for organ removal.…”
Section: Introductionmentioning
confidence: 99%
“…There is no such thing as "presumed consent" as s.15 of the Code of Practice of the Human Tissue Act 2004 clearly reminds us. 3 The General Medical Council eventually found 46 out of the 48 charges proven against Professor van Velzen, struck him off the Register and he returned to the Netherlands.…”
mentioning
confidence: 99%